The mental health of breast cancer survivors and their adolescent daughters. Issue 6 (4th July 2012) - Inbar, Cohen; Ety, Berant; Ayala, Hubert; Tamer, Perez
Abstract Objective This study examines associations between attachment orientations and mental health among breast cancer survivors and their adolescent daughters, while focusing on intergenerational transmission of emotional problems. Methods A total of 58 breast cancer survivors and their adolescent daughters were recruited 8 months following mothers' completion of treatment and were compared with a matched control group of 48 healthy mothers and their adolescent daughters. Measures included the Experiences in Close Relationships scale and the Mental Health Inventory. Results Hierarchical regressions revealed the following: First, breast cancer survivors reported higher levels of mental distress and lower levels of well‐being than control women, and the effect of breast cancer on well‐being was significant only among highly anxiously attached women. Second, daughters of breast cancer survivors reported higher levels of mental distress than daughters of control women only if they scored high on avoidant attachment. Third, daughters of breast cancer survivors reported higher levels of mental distress than daughters of control women only if their mothers scored high on anxious attachment. Conclusions Breast cancer had detrimental effects on survivors' well‐being and daughters' distress mainly when survivors scored high on attachment anxiety. Breast cancer had also detrimental effects of daughters' distress mainly when daughters scored high on avoidant attachment. These findings highlight the importance of attachment security as an inner resource for buffering detrimental mental health effects of breast cancer among survivors and their daughters.Copyright © 2012 John Wiley & Sons, Ltd.